Analysis of Key Technologies for Satellites Oriented to the Fusion of Communication, Navigation, Remote Sensing and Computing - LI Jie; XIAO Qianli; FENG Jianyuan; ZHANG Cheng (天地一体化信息网络)
After the in-depth development of space technology, the user's requirement for space system will be anintegrated space-based information service system that integrates communication, remote sensing and navigation satellites in order to provide the user with service capabilities such as high-speed data transmission, real-time remote sensing services directly to the user, high-precision positioning and navigation accurate within centimetres, and distributed collaborative computational resources, so as to be applied to a rich variety of service scenarios. However, existing communication, navigation and remote sensing satellites have barriers in terms of software protocols and physical facilities, which prevent them from integrating applications and are far from meeting the requirements for the construction of space-based information service systems. Therefore, it is necessary to study the fusion of communication, navigation, remote sensing and computation on satellites. The key points of fusion are schedulable and shareable hardware and software resources, and high-efficiency high-stability payload devices. Based on thes, the paper introduced and analyzed the key technology oriented to the fusion, and analyzed the typical application service mode of communication, navigation, remote sensing and computation fusion. Simulation experiments verified the performance enhancement after fusion.